KEBIJAKAN PEMERINTAH RUSIA MEMAKSA UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) KELUAR DARI RUSIA TAHUN 2012 - Rahmadani, Ulvia; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains about the repressive action of Russia government to pressing development of civil society in Russia through a policy to force out USAID from Russia. USAID is the greatest donor to development democracy and civil society in Russia. This research begins by explanning about relationship USAID and Russia with development of Civil Society Organization (CSO) in Russia. This research is using State and Non-Governmental Organization (NGO) relations theory. In this matter, this research is using Containment/Sabotage/Dissolution mode, which is the Russia government as Semi-Authoritarian Regime will do anything to defend national stability, include pressing development of civil society. This research uses qualitative method with techniques of writing a literature review through secondary data already available from the literature. This research shows that Russia government policy is impact to Russia NGOs because that NGOs have received assistance from USAID. Before Forcefulness out USAID from Russia by Russia government, Russia have legalized the rule to regulate about NGOs. That rule is Foreign Agents Law have legalized in July 2012. Foreign Agents Law is reaction to increased civil society activity in last 2011 until early 2012. This research shows that Russia NGO is suffer as result Forcefulness out USAID from Russia is Golos as independent association of monitoring election is just one in Russia. Golos is association pro-democracy and opposes Putin‟s government. Basic of government policy to USAID is debilitate all of NGOs pro-democracy and opposes Putin‟s government.Keywords: USAID, Civil Society, Semi-Authoritarian Regime, Democratization, Foreign Agents Law, Putin‟s Government.